Chemical Profiling of Lobelia chinensis with High-Performance Liquid Chromatography/Quadrupole Time-of-Flight Mass Spectrometry (HPLC/Q-TOF MS) Reveals Absence of Lobeline in the Herb - Haixing Wang; Yuanyuan Li; Yeqing Huang; Chunyan Zhao; Hon-Yeung Cheung (Molecules, 2018)
Lobelia chinensis is a kind of herbal medicine widely distributed and used in Asia. The chemical components of this herb, however, have not been well studied until now. Lobeline, as an essential and famous bioactive compound in Lobelia genus, has been assumed to be present in L. chinensis. In order to ascertain its presence and, more importantly, proper use of this herb, chemical profiling this herb with highly sensitive and high-resolution analytical mass spectrometry was applied. In this study, high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (HPLC/Q-TOF MS) method was employed to systematically profile the chemical constituents of L. chinensis for the first time. Comparative chemical profiling study of L. chinensis and Lobelia inflata was also conducted to provide evidence whether lobeline is present or not. Piperidine alkaloids except for lobeline, alkaloid-lignan hybrids, flavonoids, polyacetylenes, nonanedioic acid, and some new phytochemicals were successfully identified in L. chinensis simultaneously. Comparing to the chemical profiles of L. inflata, lobeline was found to be absent in L. chinensis. All of the secondary metabolites in L. chinensis were determined with the HPLC/Q-TOF MS method. The absence of lobeline in L. chinensis was confirmed after this extensive study.